European experience in implementation of electronic government - Reshetova, Hanna (Management and Entrepreneurship: Trends of Development, 2023)
Recently, it is impossible to imagine the development of countries, territories and society as a whole without the latest information technologies. Today, many countries of the world, including European countries, use such a form of public administration as e-government, which is becoming an important tool for interaction between central and local authorities, business and society. In order to achieve a high level of democracy, as well as in the conditions of a democratic society, the introduction of electronic governance becomes a necessity. This is exactly what our country, which has a high potential and all the possibilities for the introduction of electronic governance and the transfer of almost all services, especially administrative ones, to an electronic format, strives for. Electronic governance is one of the priority areas of modernization of public administration in the EU countries. The science of public administration is in constant development and the search for more effective methods, principles and means of public administration that are adequate to modern conditions and needs. In recent years, the theory and methodology of e-government has been replaced by more modern ones. In Ukraine, e-government is developing through the implementation of projects and the cooperation of all state and local self-government bodies with the support of international partners. Specialists in the field of information technologies believe that e-government is the key to reforms in Ukraine, because it is impossible to achieve high rates of transformation without the introduction of digital technologies in every sphere. At this stage, the most common area is electronic services in the field of e-government, since they concern every citizen of the country. JEL Classification: H56, О10, О40